Digitalization of Global Economy: A Qualitative Study Exploring Key Indicators use to measure digital progress in the Public sector - Febiri, Frank; Hub, Miloslav (EDP Sciences - Web of Conferences, 2021)
Research background: The digitalization of the global economy is the most common phenomenon in the 21st century. Most Public sector organizations have already started their journeys towards digitalization, and many of them have dealt with their contemporary challenges with success. At the center of these transformations are metrics and indicators used for evaluating digital progress. Already existing measures focus on numerical measures of the presence of digital technology in the public sector (output measures), but do not evaluate the quality of the digitalized public sector (outcome measures). Purpose of the article: This paper attempts to evaluate metrics and indicators used for measuring the digital progress in the public sector. Methods: Three particular aspects of digitalization in the top five leading countries (Finland, Sweden, Denmark, Netherlands, and Malta) were examined: I. success rate of public sector IT projects (measured by how often projects are scrapped); II. The price comparability between the public sector and private sector IT projects; and III. The relative modernity of government IT systems (compared to private sector systems). Findings & Value added: The findings of this paper present key metrics and indicators that can be used to evaluate public sector digital progress. Policymakers will need to redefine digitalization goals and areas of investments, while researchers can contribute more insights to the individual impact of these metrics and indicators on the development of a digital public sector. To this end, the paper contributes to a better understanding of the essential metrics and indicators to measure digitalization progress in the public sector.
Digitalizace globální ekonomiky: Kvalitativní studie zkoumající klíčové ukazatele, které se používají k měření digitálního pokroku ve veřejném sektoru
Keywords: digitalization; public sector; digital progress; digital economy; information technology